Accelerated aging in adults with knee osteoarthritis pain: consideration for frequency, intensity, time, and total pain sites - Kimberly T. Sibille; Huaihou Chen; Emily J. Bartley; Joseph Riley, III; Toni L. Glover; Christopher D. King; Hang Zhang; Yenisel Cruz-Almeida; Burel R. Goodin; Adriana Sotolongo; Megan E. Petrov; Matthew Herbert; et al. (PAIN Reports, 2017)
Abstract. Introduction:. Individuals with osteoarthritis (OA) show increased morbidity and mortality. Telomere length, a measure of cellular aging, predicts increased morbidity and mortality. Telomeres shorten with persisting biological and psychosocial stress. Living with chronic OA pain is stressful. Previous research exploring telomere length in people with OA has produced inconsistent results. Considering pain severity may clarify the relationship between OA and telomeres. Objectives:. We hypothesized that individuals with high OA chronic pain severity would have shorter telomeres than those with no or low chronic pain severity. Methods:. One hundred thirty-six adults, ages 45 to 85 years old, with and without symptomatic knee OA were included in the analysis. Peripheral blood leukocyte telomere length was measured, and demographic, clinical, and functional data were collected. Participants were categorized into 5 pain severity groups based on an additive index of frequency, intensity, time or duration, and total number of pain sites (FITT). Covariates included age, sex, race or ethnicity, study site, and knee pain status. Results:. The no or low chronic pain severity group had significantly longer telomeres compared with the high pain severity group, P = 0.025. A significant chronic pain severity dose response emerged for telomere length, P = 0.034. The FITT chronic pain severity index was highly correlated with the clinical and functional OA pain measures. However, individual clinical and functional measures were not associated with telomere length. Conclusion:. Results demonstrate accelerated cellular aging with high knee OA chronic pain severity and provide evidence for the potential utility of the FITT chronic pain severity index in capturing the biological burden of chronic pain.